H2-rich and tar-free downstream gasification reaction of efb by using the malaysian dolomite as a secondary catalyst - Mohammed M.A.A.; Shafizah I.N.; Salmiaton A.; Arifin N.A.; Hafriz R.S.R.M.; Azlina W.A.K.G.W.; Taufiq-Yap Y.H.; Shamsuddin A.H. (MDPI, 2023)
In this study, Malaysian dolomites as secondary catalysts are placed at the downstream of the fluidized-bed gasifier. Three types of Malaysian dolomites with different elemental ratios of CaO-MgO content denoted as P1, P2, and P3 are investigated with EFB gasification reaction at different cracking temperatures (700900?C). The performance of the catalysts with a variation of catalyst to biomass weight ratio (C/B) (0.05 to 0.30 w/w) is evaluated. The findings showed that the total gas yield increased by 20%, hydrogen increased by 66%, along with an almost 99% reduction in tar content with P1 catalyst with the following reaction conditions: gasification temperature of 850?C, equivalence ratio (ER) of 0.25, and cracking temperature of 900?C. Malaysia dolomite could be a secondary catalyst to provide a better alternative, tar-free hydrogen-rich gas with the possibility of regeneration and re-use. 2021 by the authors. Licensee MDPI, Basel, Switzerland.